Surface Centres for CO Adsorption on Supported Platinum - Zenon Sarbak (Adsorption Science & Technology)
Adsorption centres of platinum supported on low- and high-surface area γ-Al 2 O 3 (LSA and HAS, respectively), as well as on SiO 2 , are described. The interaction between platinum and CO was characterised and the platinum dispersion determined.